Early Survivorship, Clinical and Radiographic Outcomes Following Primary and Revision Total Ankle Arthroplasty using a Modular Augmented Revision (INVISION) Implant - Jennifer Purnell MD, FRCSC; Isabel Shaffrey; Jonathan Deland MD; Scott J. Ellis MD; Constantine Demetracopoulos MD; Jensen K. Henry MD (Foot & Ankle Orthopaedics, 2023)
Category: Ankle Arthritis; Ankle Introduction/Purpose: As the number of total ankle replacements (TAR) performed annually increases, there is an increased demand for implants that can be used in revision scenarios when primary TARs fail. As indications for TAR expand, there is increased reliance on modular systems to treat challenging conditions including bone loss, avascular necrosis, and instability. The INVISION Total Ankle Arthroplasty System (Wright Medical Technology/Stryker, Memphis, TN), released in 2018, includes modular augmented tibial trays and talar plates of varied heights to compensate for bone loss. There is limited data on early survivorship and clinical outcomes of the INVISION. This novel study aims to determine the early implant survivorship, complications, patient-reported outcomes (PROMIS), and radiographic outcomes of the INVISION implant used in both the primary and revision arthroplasty setting. Methods: This study is a single-institution retrospective review of adult patients who underwent primary or revision TAR with the INVISION implant with minimum 2-year follow-up. Demographics, reason for use of INVISION, surgical data, complications, pre- operative and 2 year post-operative radiographic data, and pre-operative and 2-year post-operative patient-reported outcome scores were collected. The primary outcome was survivorship (retention of both tibial/talar components at final follow-up). Secondary outcomes were reoperation (return to OR with retention of both tibial and talar components), radiographic complications (peri-implant lucency, cysts, or subsidence), and patient-reported outcomes (PROMIS pre-operative and 2-year post-operative). PROMIS scores were collected across the following domains: physical function, pain interference, pain intensity, global mental health, and depression score. Results: Twenty-six patients (primary=7; revision=19) underwent INVISION TAR (mean age 62 years, weight 81.kg, BMI 29.3 kg/m 2 , 15/26 male) with mean follow-up 3.5 years. Reason for INVISION primary TAR included tibial (n=1) or talar (n=5) bone loss, and take-down fusion (n=1); INVISION revision TAR was used for tibial (n=6) or talar (n=7) component subsidence, recurrent tibiotalar malalignment (valgus=1, varus=3), and post-infection bone loss (n=2). Two-year implant survivorship was 100%. There were 2 reoperations (7.7%): 1 gutter debridement and 1 irrigation, debridement and polyethylene exchange for infection. Two-year follow-up PROMIS domains improved significantly (p < 0.05) from pre-operative in both the primary (pain interference, pain intensity) and revision cohorts (pain interference, pain intensity, global physical function). Two-year radiographic follow-up yielded 1 tibial peri-implant lucency and 1 tibial cyst. Conclusion: In this single-institution series, there was excellent short-term survivorship of the INVISION TAR implant with no failures in primary or revision cases. There were significant improvements in patient-reported outcomes scores. There were low rates of peri-implant lucencies and cysts. The results of this study support the use of the INVISION implant in both the complex primary and revision TAR setting. INVISION may offer an alternate surgical solution to fusion, custom printed cage implants, and total talus replacement in this complex patient population. Further research and follow-up data are warranted to report the longer-term outcomes and survivorship of this implant.